PENGHIDUPAN PELAKU USAHA PARIWISATA PASCA ERUPSI GUNUNG MERAPI TAHUN 2010 PENDUDUK DESA HARGOBINANGUN, KECAMATAN PAKEM, KABUPATEN SLEMAN - , AMI MARDOTILLAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Strategy is needed to survive. Hargobinangun resident have varied livelihood in the tourism service sector, that is accomodation business, Jeep tours, food stalls and street vendors. Socio-economic conditions of the community tourism businesses suffered shock after the eruption of Merapi in 2010. This research aims to: 1. Identify livelihood capital after the eruption in 2010, 2. Knowing strategies to survive and carry on the business after the eruption in 2010. To explain the purpose, researchers use qualitative methods. The main data used are primary data obtained from the in-depth interview respondents, the business tourism in three village areas of research. Respondents were selected using purposive sampling method. The collected data will be made descriptive analysis, and assisted in the discussion using frequency tables and images. The results showed that 95% of people in tourism businesses continue their business in the tourism sector. Livelihood capital used are natural capital, human capital, financial capital, social capital, and physical capital. Livelihood Capital are most negatively affected is financial capital. A year after the eruption, tourism activity was unstable, the number of tourists who visit come down drastically, and made their income unstable too. Livelihood strategies used by residents include, strategy for capital, attention strategy, and strategy to improve the quality. Strategy that has been chosen by the people to survive is saving and live frugally, as well as find information about the state of their environment, and to innovate in the field of business they run. To continued their business, as well as residents use private funds to cooperatives and bank borrowing. One of the accomodation and jeep tourism owners strategy is going into an organization of tourism to get high theirself quality.